'For six days I’ve only dreamt of Lancelot' – Early modern reception of the Middle Ages between castles in the air and dusty tomes (KULT_online, 2014)
In this volume, Michèle Guéret-Laferté and Claudine Poulouin bring together several articles concerning early modern ways of access to medieval – essentially belletristic – literature. Assuming one common perspective, the authors aim to examine the modalities of text transmission. By means of this priority shift to the external imposed conditions of reception, the anthology constitutes a well-founded, epoch-crossing counterpart to existing studies concerning literary representations of the Middle Ages.